A venous mechanism of ventriculomegaly shared between traumatic brain injury and normal ageing - Aso, Toshihiko; Sugihara, Genichi; Murai, Toshiya; Ubukata, Shiho; Urayama, Shin-ichi; Ueno, Tsukasa; Fujimoto, Gaku; Thuy, Dinh Ha Duy; Fukuyama, Hidenao; Ueda, Keita (Brain (London, England : 1878), 2020)
Recently, age-related timing dissociation between the superficial and deep venous systems has been observed; this was particularly pronounced in patients with normal pressure hydrocephalus, suggesting a common mechanism of ventriculomegaly. Establishing the relationship between venous drainage and ventricular enlargement would be clinically relevant and could provide insight into the mechanisms underlying brain ageing. To investigate a possible link between venous drainage and ventriculomegaly in both normal ageing and pathological conditions, we compared 225 healthy subjects (137 males and 88 females) and 71 traumatic brain injury patients of varying ages (53 males and 18 females) using MRI-based volumetry and a novel perfusion-timing analysis. Volumetry, focusing on the CSF space, revealed that the sulcal space and ventricular size presented different lifespan profiles with age; the latter presented a quadratic, rather than linear, pattern of increase. The venous timing shift slightly preceded this change, supporting a role for venous drainage in ventriculomegaly. In traumatic brain injury, a small but significant disease effect, similar to idiopathic normal pressure hydrocephalus, was found in venous timing, but it tended to decrease with age at injury, suggesting an overlapping mechanism with normal ageing. Structural bias due to, or a direct causative role of ventriculomegaly was unlikely to play a dominant role, because of the low correlation between venous timing and ventricular size after adjustment for age in both patients and controls. Since post-traumatic hydrocephalus can be asymptomatic and occasionally overlooked, the observation suggested a link between venous drainage and CSF accumulation. Thus, hydrocephalus, involving venous insufficiency, may be a part of normal ageing, can be detected non-invasively, and is potentially treatable. Further investigation into the clinical application of this new marker of venous function is therefore warranted.